The Mathematical Propriety of Accounting Measurements and Calculations. - Lim, Ronald S. (The Accounting Review, 1966)
Abstract In this article the author investigates the mathematical propriety of accounting measurement and calculations. The author has seen that the ratio scale and mathematical fields govern the mathematical propriety of accounting measurement and calculation, respectively. Given that p is the property to be measured and F the set of items a, b, c, ... possessing property p, one can quantify the content of property p in each item of F. A substantial portion of the problem of accounting measurement was then reduced to determining p and m(F).